Leishmania major RUVBL1 has a hexameric conformation in solution and, in the presence of RUVBL2, forms a heterodimer with ATPase activity - Abrahao, Josielle; Amaro, Barbara T.; Peres, Barbara R.; Quel, Natalia G.; Araga, Annelize Z. B.; Morea, Edna G. O. [UNESP]; Cano, Maria Isabel N. [UNESP]; Houry, Walid A.; Ramos, Carlos H. I. (Elsevier B.V., 2021)
ATPases belonging to the AAA+ superfamily are associated with diverse cellular activities and are mainly characterized by a nucleotide-binding domain (NBD) containing the Walker A and Walker B motifs. AAA+ proteins have a range of functions, from DNA replication to protein degradation. Rvbs, also known as RUVBLs, are AAA+ ATPases with one NBD domain and were described from human to yeast as participants of the R2TP (Rvb1-Rvb2-Tah1-Pih1) complex. Although essential for the assembly of multiprotein complexes-containing DNA and RNA, the protozoa Rvb orthologs are less studied. For the first time, this work describes the Rvbs from Leishmania major, one of the causative agents of Tegumentar leishmaniasis in human. Recombinant LmRUVBL1 and LmRUVBL2 his-tagged proteins were successfully purified and investigated using biophysical tools. LmRUVBL1 was able to form a well-folded elongated hexamer in solution, while LmRUVBL2 formed a large aggregate. However, the co-expression of LmRUVBL1 and LmRUVBL2 assembled the proteins into an elongated heterodimer in solution. Thermo-stability and fluorescence experiments indicated that the LmRUVBL1/2 heterodimer had ATPase activity in vitro. This is an interesting result because hexameric LmRUVBL1 alone had low ATPase activity. Additionally, using independent SL-RNAseq libraries, it was possible to show that both proteins are expressed in all L. major life stages. Specific antibodies obtained against LmRUVBLs identified the proteins in promastigotes and metacyclics cell extracts. Together, the results here presented are the first step towards the characterization of Leishmania Rvbs, and may contribute to the development of possible strategies to intervene against leishmaniasis, a neglected tropical disease of great medical importance.
Keywords: Rvb; Leishmania major; AAA plus protein; DNA helicases; ATPase